Cover Feature: Making Aromatic Phosphorus Heterocycles More Basic and Nucleophilic: Synthesis, Characterization and Reactivity of the First Phosphinine Selenide (Chem. Eur. J. 50/2021). Issue 50 (13th August 2021) - Wossidlo, Friedrich; Frost, Daniel S.; Lin, Jinxiong; Coles, Nathan T.; Klimov, Katrin; Weber, Manuela; Böttcher, Tobias; Müller, Christian
Abstract : The very low basicity and nucleophilicity of the phosphorus donor in phosphinines can be drastically increased by introducing strongly σ‐donating Me3 Si substituents to the aromatic phosphorus heterocycle. The highest gas‐phase basicity was found for 2, 3, 5, 6‐tetrakis(trimethylsilyl)phosphinine, which is even more basic in the gas phase than pyridine. This finding led to the first quantitative synthesis of a phosphinine selenide by treating red selenium with 2, 6‐bis(trimethylsilyl)phosphinine. More information can be found in the Full Paper by T. Böttcher, C. Müller, et al. (DOI: 10.1002/chem.202102390 ).